Building adaptive performance through knowledge competence, organizational culture, and perceived organizational support - Sri Wahyu Lelly Hana Setyanti; Singgih Bektiarso; Muhammad Ilham Naufal; Deki Zulkarnain (Manajemen dan Bisnis, 2026)
This study aims to examine the determinants of adaptive performance, namely knowledge competence and organizational culture with the mediation of perceived organizational support. This study uses explanatory research with a population of MSMEs in Jember Regency with a sampling of 295 respondents spread across various types/categories of MSMEs. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 was used to test the suggested study model. The findings show that knowledge competence and organizational culture significantly improve adaptive performance, both directly and indirectly through perceived organizational support. Through the integration of knowledge competency and organizational culture as important antecedents and the positioning of perceived organizational support as a mediating mechanism, this study enhances the theoretical understanding of adaptive performance. To improve employees' capacity to adaptive performance, MSME owners and managers should make investments in ongoing knowledge competence and foster an adaptable organizational culture. Long-term competitiveness can also be strategically enhanced by bolstering perceived organizational support through equitable treatment, acknowledgment, and sufficient resources.